Industrial education for girls - Romick, Agnes (My University, 1893)
Introduction: Education is not a giving of something to somebody. It is a bringing forward or a bringing into use of the faculties with which every well born human being is endowed by nature. All nature shows a spontaneous activity which makes itself felt all through life. This activity must be the foundation upon which all education is built and if fully trained will guide all work to a desired end and make every day of life one of usefulness.
Citation: Romick, Agnes. Industrial education for girls. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Education; Nature; Life; Theses; Manuscripts (documents)